The Effect of Using Digital Technology on the Effectiveness of Rank Promotion Services at the Regional Personnel Board (BKD) of the Special Region of Yogyakarta - Herlambang, Susatyo; Muhammad Isnaini Fathoni (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of the use of digital technology on the effectiveness of promotion services at the Badan Kepegawaian Daerah (BKD) Special Region of Yogyakarta. The data collection method was carried out through questionnaires which were distributed to 52 respondents consisting of employees at BKD Yogyakarta Special Region who had used digital technology services. Data analysis was performed using a simple linear regression analysis technique. The results of the study show that the use of digital technology has a significant effect on the effectiveness of promotion services at BKD, Special Region of Yogyakarta. The regression coefficient value shows a positive and significant number between the variable use of digital technology (X) and the effectiveness of promotion services (Y). Based on the results of this study, it is suggested that BKD Special Region of Yogyakarta increase the use of digital technology in promotion services to improve service effectiveness.